1980
DOI: 10.3171/jns.1980.52.3.0414
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar astrocytoma invading the musculature and soft tissues of the neck

Abstract: A case of cerebellar astrocytoma with unusual growth pattern in an 8-year-old boy is reported. The tumor had some histological hallmarks of malignancy (focally high cellularity, mitotic figures, necroses, and calcifications) and, 17 months after subtotal removal, recurred as a nuchal mass in the area of the incision, infiltrating first the skeletal musculature and later other soft tissues of the neck, including lymph nodes. Although cerebellar astrocytomas may recur locally and some may even seed through the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although malignant transformation was blamed to play a role in the progression of PAs, postmortem examinations and biopsies mostly established that malignant transformation does not seem to be evident in PAs with LMD [6, 10, 12, 23, 25]. Although multicentric spread indicates a more aggressive variant of PA, the slow-growing potential of PA persists after the occurrence of LMD [10, 16, 22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although malignant transformation was blamed to play a role in the progression of PAs, postmortem examinations and biopsies mostly established that malignant transformation does not seem to be evident in PAs with LMD [6, 10, 12, 23, 25]. Although multicentric spread indicates a more aggressive variant of PA, the slow-growing potential of PA persists after the occurrence of LMD [10, 16, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Mamelak et al [1 ]pointed out an incidence of LMD of 30% in hypothalamic PAs. Over the years, case reports of PAs with LMD – 25% synchronously and 75% 2 years after initial diagnosis – were treated in a wide range of options [6, 10, 12, 16, 23, 25] for their spinal (30%), cranial (33%) and combined (37%) metastases. In 70% of these cases, the primary tumor was located in the chiasmo-hypothalamic region and in 30% in the cerebellar region.…”
Section: Discussionmentioning
confidence: 99%
“…This patient received aggres sive therapy with chemotherapy and radiation therapy without evidence of disease progression over 4.5 years. Kepes et al [55] described a similarly mixed histological pattern with rapid disease progression, demonstrating the activity of the anaplastic region. Ringertz et al [56] reported a malignant recurrence with rapid disease pro gression 22 months after resection of a pilocytic astrocy toma which contained densely cellular areas with necrot ic regions.…”
Section: Recurrence and Anaplastic Change In Pilocytic Astrocytomasmentioning
confidence: 99%
“…The small number of cases reported in the literature have generally described the use of radiotherapy, with no clear proof of efficacy. A number of investigators have found apparent benefit following radiation therapy [ 1 1,13,16], though other have described disease progression [14,15,18,22]. The uncertain benefit of radiation therapy in this uncommon clinical setting, along with its long-term sequelae in the pediatric patient population [7], provide a rationale for exploring alternate therapeutic modalities.…”
Section: Disc U Sslo Nmentioning
confidence: 99%